The Lead (Pb) Concentration in Oysters and the Un-Safe Health Risk inCommunities around Coastal areas Balikpapan, East Kalimantan - Bekti Ananda Febriani; Blego Sedionoto; Ismail Fahmi Almahdi (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : The hygiene and sanitation conditions of traditional markets are essential for ensuring community food safety. The Beluluq Lingau Thematic Market in Samarinda City promotes local Dayak culture and offers both general and traditional East Kalimantan foods Objective : This study aimed to describe food hygiene and sanitation conditions at Beluluq Lingau Market and to assess microbiological quality based on the coliform parameter Research Methods/ Implementation Methods : This research used an analytical descriptive design with a cross-sectional approach. Samples were total sampling from 6 food stalls and 10 food handlers. Data were collected through observation and interviews using inspection form from the Indonesian Ministry of Health (Peraturan Pemerintah No. 66/2014). Microbiological analysis was conducted on seven food samples using secondary data from Puskesmas Sempaja from routine monitoring with sanitarian kit. The parameters tested included total coliform and Escherichia coli. Results : Result showed that 50% of food stalls did not meet hygiene and sanitation requirements. The unmet aspects included covered waste bins (100%), use of masks and aprons (100%), and vector control (100%). A total of five out of seven food samples (71.4%) tested positive for coliform, with bacterial counts exceeding 100, two negative samples were traditional snacks wrapped in plastic and leaves. Conclusion/Lesson Learned : Food stalls at the Beluluq Lingau Market still require improvement in hygiene and sanitation to prevent microbiological contamination. Strengthening food safety training and ensuring the availability of sanitation facilities such as food covers during serving, personal protective equipment, and covered waste bins are essential